Reconnoitering Settler Colonization Part I: Its Philosophy and Praxis - Tushima, Cephas T. A. (Research Developments in Arts and Social Studies Vol. 5, 2022)
The survey broaches colonial studies, poststructuralism (with its emphasis on the use of language [rhetorics] as a means for understanding, dominating, subjugating others), and the subsequent rise of postcolonial studies. This survey highlights the weaknesses of postcolonial studies, not the least, its pursuit of theoretical consistency at the detriment of cultural and historical specificity, being enmeshed in pastness, and the obfuscation of thriving settler colonial states or situations in contemporary societies. Arising from this, the embark upon a study of the global phenomenon of settler-colonization from the biblical era to the contemporary time, particularly examining its nature, ideology, processes, and praxis. The methodology used is literary and historical analysis, and the theoretical framework is based on the burgeoning area of settler-colonial studies. This essay lays the groundwork for Part II of the study, which will apply settler-colonial studies to the Nigerian situation.